Building safe, secure and sustainable futures in the South China Sea. Issue 1 (2nd January 2020) - Lim, Michelle
ABSTRACT: This essay argues that by framing security in the South China Sea through the lens of territorial claims and power relations the bigger picture of a safe, secure and sustainable South China Sea is neglected. The essay reflects on a photograph from my childhood on the shores of the South China Sea. In the photograph, I have a little red bucket in my hands and a wide grin on my face as I prepare to build a sandcastle. In the intervention, I recall how it feels to be truly secure. By returning to the joys of childhood experienced on the shores of the South China Sea, I consider what future generations require of current leaders. I highlight the unique environmental heritage of the South China Sea (one of the most biologically diverse sea areas in the world) and the livelihood and nutrition needs of the large populations that the South China Sea supports. From there, I set out a vision for peaceful and sustainable futures in the South China Sea grounded in appreciation of shared heritage and the imperative of continued collaboration.